In Vitro Evaluation of the Genotoxic Activity and Apoptosis Induction of the Extracts of Roots and Leaves from the Medicinal Plant Coccoloba mollis (Polygonaceae) - Tsuboy, Marcela S.; Marcarini, Juliana C.; Luiz, Rodrigo C.; Barros, Iuri B.; Ferreira, Dalva T.; Ribeiro, Lucia R. [UNESP]; Mantovani, Mario S. (Mary Ann Liebert, Inc., 2010)
Coccoloba mollis (Family Polygonaceae) is a medicinal plant popularly used in cases of memory loss, stress, insomnia, anemia, impaired vision, and sexual impotence, but the scientific literature, to date, lacks studies on the biological effects of this species, particularly with regard to cytotoxicity and induction of DNA damage. The aim of the present study was to assess in vitro (in hepatic HTC cells) ethanolic extracts of the roots and leaves of C. mollis for cytotoxicity, genotoxicity, and induction of apoptosis. For these evaluations the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cytotoxicity assay, comet assay, micronucleus test with cytokinesis block, and an in situ test for detection of apoptotic cells with acridine orange staining were used. The results showed that the extract obtained from the roots of C. mollis is more cytotoxic than that obtained from the leaves and that the reduction in cell viability observed in the MTT assay was a result, at least in part, from the induction of apoptosis. Both extracts induced DNA damage at a concentration of 20 mu g/mL in the comet assay, but no genotoxicity was detected with any of the treatments carried out in the micronucleus test.
Keywords: apoptosis; Coccoloba mollis; cytotoxicity; genotoxicity; herbal extract; Polygonaceae